2010
DOI: 10.1007/s11738-010-0625-4
|View full text |Cite
|
Sign up to set email alerts
|

Effect of salinity on germination, phytase activity and phytate content in lettuce seedling

Abstract: Seeds of four lettuce (Lactuca sativa L.) varieties (Romaine, Augusta, Vista and Verte) differing in their salt sensitivity were sown at 0 (Control), 50, 100 and 150 mM NaCl. The final germination percentage decreased with the increasing salinity and was annulated at the highest salt concentration in Vista and Verte, the most sensitive varieties. However, in the less sensitive ones, Romaine and Augusta, it was slightly modified at 50 and 100 mM NaCl and then decreased by 50% compared with the control, at 150 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
38
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 35 publications
2
38
0
Order By: Relevance
“…It has been reported that GA functions in diametrically opposed capacities in response to abiotic stresses. GA is involved in stress tolerance during germination and seedling establishment (Kabar and Baltepe, 1990;Kaur et al, 1998;Nasri et al, 2011), whereas it is involved in stress intolerance in established vegetative tissues (Sarkar et al, 2004;Achard et al, 2006). In the tissues of Arabidopsis, DELLA/RGA-LIKE3 is induced by the transcriptional activator AtCBF1/DREB1B in response to cold and water deprivation (Achard et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that GA functions in diametrically opposed capacities in response to abiotic stresses. GA is involved in stress tolerance during germination and seedling establishment (Kabar and Baltepe, 1990;Kaur et al, 1998;Nasri et al, 2011), whereas it is involved in stress intolerance in established vegetative tissues (Sarkar et al, 2004;Achard et al, 2006). In the tissues of Arabidopsis, DELLA/RGA-LIKE3 is induced by the transcriptional activator AtCBF1/DREB1B in response to cold and water deprivation (Achard et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…GA functions to mediate both tolerance and intolerance pathways involved in the responses to different abiotic stresses. Application of exogenous GA to plant seeds reverses the salt stress-and heat stress-induced inhibition of germination and seedling establishment (Kabar and Baltepe, 1990;Kaur et al, 1998;Nasri et al, 2011). By contrast, salt stress in Arabidopsis (Arabidopsis thaliana) seedlings leads to a decrease of GA levels, the accumulation of DELLA proteins, and the suppression of plant growth, which ultimately confers tolerance to stress (Achard et al, 2006).…”
mentioning
confidence: 99%
“…One unit of enzyme activity is defined as amount of enzyme liberating 1 nmol of p-nitrophenol per minute (Saluja et al, 1989). Phytase activity was performed by measuring the release of phosphate from sodium phytate and was carried as previously described (Nasri et al, 2011).…”
Section: Extraction and Assay Of Acid Phosphatase And Phytasementioning
confidence: 99%
“…This lettuce variety, Vista, employed in this study was selected as representative of the most sensitive variety to salt under salt treatment in germination step (Nasri et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Several authors have shown that, pepper, is sensitive or moderately sensitive, to salinity during different growth stages (Pascale et al, 2003). It has also been shown that salinity caused a decrease in FG% of lettuce seeds (Nasri et al, 2010).…”
Section: Introductionmentioning
confidence: 99%